2020
DOI: 10.3389/fpsyt.2020.575755
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on the Castile and Leon Addiction Treatment Network: A Real-Word Experience

Abstract: Background: Patients suffering from addiction are a vulnerable group in the midst of COVID-19, so their healthcare is considered essential. In this paper, the measures and responses of the Drug Addiction Assistance Network of Castile and Leon (DAACYL) in Spain during the first 6 weeks of the COVID-19 pandemic are explained. The aim is that this experience could be useful in places where this problem will continue and could help future interventions.Methods: A telephone survey was carried out as the main method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 33 publications
(56 reference statements)
3
32
0
1
Order By: Relevance
“…It is likely that some patients transferred their drinking in bars and restaurants to their homes, including drinking socially through digital channels; however, patients who reduced their consumption could have taken advantage of the confinement to avoid consumption. These data coincide with other Spanish studies carried out in SUD patients during this time [ 5 , 20 ]. It also aligns with some studies carried out in the general population that found increased benzodiazepine and alcohol consumption [ 9 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is likely that some patients transferred their drinking in bars and restaurants to their homes, including drinking socially through digital channels; however, patients who reduced their consumption could have taken advantage of the confinement to avoid consumption. These data coincide with other Spanish studies carried out in SUD patients during this time [ 5 , 20 ]. It also aligns with some studies carried out in the general population that found increased benzodiazepine and alcohol consumption [ 9 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another study, using hair analysis, conducted on 30 subjects, showed a decrease in the consumption of illegal drugs but a significant increase in consumption of benzodiazepines and alcohol, substances which are more easily accessible [21]. These data were confirmed in a separate study from Spain which found an increase in alcohol and benzodiazepine consumption in drug-dependent individuals [5]. Few studies include illegal substance use among patients with SUD.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Having identified the most at risk population, more targeted and effective prevention strategies could be more easily be implemented, even more importantly during periods of personal confinement. Some reinforcement programs on addiction health care have been launched during the pandemic ( 81 ). They address behaviors other than exercise or the use of enhancement drugs, but similar initiatives could be created in the future, targeting the latter aspects as well.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, a telephone survey was conducted by the health professionals among the Drug Addiction Assistance of Castile and Leon (DAACYL) units. The professionals in the DAACYL units expressed that the clinical impact during the first six weeks of the pandemic was moderate; however, six centers reported that patients increased or started consuming alcohol and benzodiazepines, especially alprazolam [62]. Among people who were confirmed with coronavirus infection and discharged subsequently, there was a 3.3% initiation of new benzodiazepine prescriptions [63].…”
Section: Discussionmentioning
confidence: 99%